GEOPHYSICAL INVESTIGATION OF GEOTHERMAL MANIFESTATION IN SUNGAI MEDANG USING ELECTRICAL RESISTIVITY AND GRAVITY METHODS - Resta, Ichy Lucya; Mahardika, Rizky; M.Z, Nazri; Hamdi, Husnul; Kusuma Dewi, Ira; Andriani, Aulia (JOURNAL ONLINE OF PHYSICS, 2025)
This study investigates the geothermal manifestation in Sungai Medang, located within a volcanic arc depression zone of the Sungai Penuh Basin, formed by right-lateral movement along the segmented Siulak Fault. The exploration approach combined electrical resistivity and gravity methods to delineate subsurface features associated with hydrothermal activity. The electrical resistivity survey employed a dipole–dipole configuration with 25-meter spacing over a 400-meter line and the complementary gravity data from the Topex/Poseidon satellite altimetry were processed into Simple Bouguer Anomaly (SBA) maps. Resistivity survey revealed low-resistivity zones (11.6–99.1 Ωm), interpreted as hydrothermal fluid pathways and altered volcanic formations aligned with known fault traces, particularly the Siulak Fault segment. The gravity data indicated NW–SE trending density contrasts. Spectral analysis identified residual anomalies (~1.5 km depth) consistent with shallow sedimentary infill and structural depressions, while deeper regional anomalies (~38.7 km) reflected basement variations. The spatial correlation of resistivity lows, gravity lows, and surface manifestations suggests active geothermal upflow along structurally controlled zones. This study highlights the importance of integrating geophysical datasets for geothermal resource evaluation and offers a methodological framework applicable to similar underexplored regions in Indonesia and beyond.